Development of Learning Media Portable Wind Direction Indicators as Visual Aids for Flight Navigation - Soleh, Asep Muhamad; Gauthama, Wira; Suhanto, Suhanto; Rifai, Mochammad; Alddi, Muhammad Dimas Bara (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
In this study, we designed a wind direction indicator learning media to help cadets understand how the equipment works. Wind direction indicator is used as a navigation tool for pilots to determine the direction of landing on the airport runway. This research was conducted at the Palembang Civil Aviation Polytechnic with research and development methods. The object of research is the cadets of the airport engineering study program. The results showed that the cadets were very enthusiastic in learning these tools, and increased their knowledge and competence in the field of visual landing aids navigation at airports. With the increase in the competence of cadets, it is hoped that it will support flight safety in Indonesia.